1991
DOI: 10.1007/bf03159928
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in blood histamine in drug-treated Parkinsonian patients

Abstract: Blood histamine and serum histaminase activity were determined in a group of patients with Parkinson disease (PD) and in a group of healthy controls. Untreated PD patients present significantly higher blood histamine than normal controls. Therapy with L-dopa + cardidopa results in a significant decrease in blood histamine. This decrease becomes more accentuated when anticholinergics are added to this therapy. No significant changes were detected in plasma histaminase. The authors suggest, as a hypothesis, that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…In contrast to previous studies that have focused on enzymes related to xenobiotic metabolism (Agundez et al 1997;Alonso-Navarro et al 2006;Martinez et al 2007), this study focuses on an enzyme involved in the degradation of endogenous substances. Several studies support a role of histamine in PD (Coelho et al 1991;Prell and Green 1991;Langlais et al 1994;Thoburn et al 1994;Anichtchik et al 2000;Agundez et al 2007), but this is the first study that provides hypothesis-generating data arguing for a role of histamine in ET, and raises the question of whether other movement disorders besides ET and PD could be related to genetic alterations of histamine metabolism.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In contrast to previous studies that have focused on enzymes related to xenobiotic metabolism (Agundez et al 1997;Alonso-Navarro et al 2006;Martinez et al 2007), this study focuses on an enzyme involved in the degradation of endogenous substances. Several studies support a role of histamine in PD (Coelho et al 1991;Prell and Green 1991;Langlais et al 1994;Thoburn et al 1994;Anichtchik et al 2000;Agundez et al 2007), but this is the first study that provides hypothesis-generating data arguing for a role of histamine in ET, and raises the question of whether other movement disorders besides ET and PD could be related to genetic alterations of histamine metabolism.…”
Section: Discussionmentioning
confidence: 89%
“…Changes in the morphology and an increase in the density of histaminergic fibers in the substantia nigra have been described in the brain of PD patients (Anichtchik et al 2000). In addition, among patients with PD, high blood histamine levels (Coelho et al 1991) and increased concentration of the histamine metabolite pros-methylimidazoleatic acid in the cerebrospinal fluid are present (Prell and Green 1991).…”
Section: Introductionmentioning
confidence: 97%
“…The rationale for this study is that histamine seems to play a role in PD (Coelho et al 1991;Prell and Green 1991;Anichtchik et al 2000), and therefore, it may be speculated that detrimental mutations at histamine-metabolising genes could be related to PD. Our findings indicate that statistically significant differences in the genotypes and allele frequencies for the HNMT genotype exist among patients with PD as compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the morphology and increase in density of histaminergic fibres in the substantia nigra have been described in brain of PD patients (Anichtchik et al 2000). In addition, among patients with PD high blood histamine levels (Coelho et al 1991) and increased concentration of the histamine metabolite pros-methylimidazoleatic acid in the cerebrospinal fluid are present (Prell and Green 1991). Taken together, these findings suggest that alterations in histamine levels may be related to PD.…”
Section: Introductionmentioning
confidence: 92%
“…Prast et al (1994) recently found histamine to increase the release of acetylcholine within the rat striatum via H2 receptors. Coelho et al (1991) demonstrated decreased blood histamine levels in drug-treated Parkinson's patients. While histamine's role in the pathophysiology of PD is unknown, it is becoming increasingly evident that the extensive histaminergic innervation within the striatum may modulate striatal output as well as dopamine and acetylcholine release.…”
Section: Discussionmentioning
confidence: 96%